on ? - statistical convergence of double sequences of order ? in topological groups - Aral, Nazlim Deniz; Kandemir, Hacer Sengul; Et, Mikail (Springernature, 2023)
We investigate the concept of rho-strongly summable and rho-statistical convergence for double sequences of order alpha in topological groups by using definition of rho-statistical convergence which was defined by Cakalli in Bulletin of the Malaysian Mathematical Sciences Society 40:1701-1710. We give some inclusion relations between these concepts.
Keywords: Topological groups; Statistical convergence; rho-statistical